Silence is sexy: soundscape complexity alters mate choice in túngara frogs. (10th November 2020) - Coss, Derek A; Hunter, Kimberly L; Taylor, Ryan C
Abstract: Many animals acoustically communicate in large aggregations, producing biotic soundscapes. In turn, these natural soundscapes can influence the efficacy of animal communication, yet little is known about how variation in soundscape interferes with animals that communicate acoustically. We quantified this variation by analyzing natural soundscapes with the mid-frequency cover index and by measuring the frequency ranges and call rates of the most common acoustically communicating species. We then tested female mate choice in the túngara frog ( Physalaemus pustulosus ) in varying types of background chorus noise. We broadcast two natural túngara frog calls as a stimulus and altered the densities (duty cycles) of natural calls from conspecifics and heterospecifics to form the different types of chorus noise. During both conspecific and heterospecific chorus noise treatments, females demonstrated similar preferences for advertisement calls at low and mid noise densities but failed to express a preference in the presence of high noise density. Our data also suggest that nights with high densities of chorus noise from conspecifics and heterospecifics are common in some breeding ponds, and on nights with high noise density, the soundscape plays an important role diminishing the accuracy of female decision-making. Abstract : For a female frog looking for a mate, a quiet night is the best time to choose a mate because it is easier to hear their calls. We show that female túngara frogs struggle to choose a mate on nights with high densities of natural chorus noise. Females are more likely to mate with less attractive males during these noisy nights, which are common occurrences at breeding ponds.